Features of the local community involvement in the social tourism development (case study – Serik district, Antalya, Turkey) - Sari, Cemali; Sehida, Kateryna; Çakir, Gamze; Telebienieva, Ievgeniia (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Introduction of the research problem. Tourism activities have shown a shift from privileged individuals with high purchasing power to individuals with lower income levels due to increased leisure time. Along with a high economic potential, tourism has an important social significance; namely, it ensures the restoration of human life forces spent in the work process and contributes to the spiritual and intellectual development of the individual, thereby increasing the quality of labor resources. Orientation to the development of tourism in view of the principles of sustainable development, with an understanding of the need for the development of social tourism and promoting the improvement of the level and quality of life of the population, ensuring accessibility for all segments of the population does not lose its relevance and the need to implement science-based initiatives and measures that should be based on specific research results, primarily geographical. In order to understand the opportunities and obstacles to the development of social tourism, the following questions remain essential: What is the attitude of the local population to the intensive development of tourism in the region of residence? What is the involvement of the local population in tourism? What problems does the local population face when organizing leisure activities? What are the obstacles, challenges, and opportunities for the organization of social tourism? Given the limited geographical studies on social tourism, this study is seen as an original and distinctive contribution. The significance of this research lies in its potential to serve as an example for Turkey. The purpose of this research is to identify the participation of the local community living in urban and rural neighborhoods of Serik district, which constitutes one of the significant destination points in Antalya province, known as the tourism capital of Turkey, in tourism activities. Additionally, if there are any factors hindering their participation, the aim is to identify and highlight them. Results, scientific novelty, practical significance. Research method was employed, and a face-to-face survey was conducted using a random sampling method between December 2022 and April 2023, reaching a total of 466 participants. Out of these, 33 surveys were used for pilot testing, and due to incomplete data, 384 surveys were entered into the SPSS software package for analysis. According to the findings, it was observed that 44.8% of the local community residing in urban and rural areas of Serik district had not had the opportunity to go on vacation in 2022 or earlier. In this context, it is evident that the most significant factor influencing the participants’ inability to go on vacation is financial insufficiency. Therefore, the necessity of public and civil institutions and organizations supporting the local population with various holiday programs arises.Therefore, it is deemed necessary to integrate social tourism activities to the maximum extent possible in the tourism planning for the local community.